Does eating family meals and having the television on during dinner correlate with overweight? A sub-study of the PRO GREENS project, looking at children from nine European countries. Issue 11 (19th March 2014) - Roos, Eva; Pajunen, Tuuli; Ray, Carola; Lynch, Christel; Kristiansdottir, Ása Gudrun; Halldorsson, Thorhallur I; Thorsdottir, Inga; te Velde, Saskia J; Krawinkel, Michael; Behrendt, Isabel; de Almeida, Maria Daniel Vaz; Franchini, Bela; et al.
Abstract: Objective: Family meals have been negatively associated with overweight in children, while television (TV) viewing during meals has been associated with a poorer diet. The aim of the present study was to assess the association of eating family breakfast and dinner, and having a TV on during dinner, with overweight in nine European countries and whether these associations differed between Northern and Southern & Eastern Europe. Design: Cross-sectional data. Schoolchildren reported family meals and TV viewing. BMI was based on parental reports on height and weight of their children. Cut-off points for overweight by the International Obesity Task Force were used. Logistic regressions were performed adjusted by age, gender and parental education. Setting: Schools in Northern European (Sweden, the Netherlands, Iceland, Germany and Finland) and Southern & Eastern European (Portugal, Greece, Bulgaria and Slovenia) countries, participating in the PRO GREENS project. Subjects: Children aged 10–12 years in ( n 6316). Results: In the sample, 21 % of the children were overweight, from 35 % in Greece to 10 % in the Netherlands. Only a few associations were found between family meals and TV viewing during dinner with overweight in the nine countries. Northern European children, compared with other regions, were significantly more likely to be overweight if they had fewer family breakfasts and more often viewed TV during dinner. Conclusions: The associations between family meals and TV viewing during dinner with overweight were few and showed significance only in Northern Europe. Differences in foods consumed during family meals and in health-related lifestyles between Northern and Southern & Eastern Europe may explain these discrepancies.